Unique Removal of a Kinked Nasogastric Tube - Narayan, Kumar Shwetanshu; Gupta, Gaurav Kumar; Nijhawan, Sandeep; Puri, Shekhar (Journal of Digestive Endoscopy, 2017)
Nasogastric (NG) tube insertion is a common clinical procedure used for both diagnostic and therapeutic purposes. As the importance of enteral nutrition is being increasingly recognized; the use of NG tube insertion has steadily increased. Here, we present an interesting case in which a kinked NG tube was removed in a unique manner with “push and pull” technique without untoward trauma.
Keywords: Esophagogastroduodenoscopy; Crohn’s disease; nasogastric tube